Demographic and socioeconomic analysis of medication use by elderly people living in rural areas - Bester Hermes, Gabriele; Lange, Celmira; Matos Lemões, Marcos Aurélio; Somavila Przylynski Castro, Denise; Weber Peters, Carla; Noema da Rosa Braga, Jéssica (O Mundo da Saúde, 2022)
The objective of this study is to analyze the association of demographic and socioeconomic characteristics related to medication use. A sample of 822 elderly people aged 60 years or older was evaluated. Data collection took place from July to October 2014. Evidence of associations between sex and medication use and age group and medication use was obtained. The prevalence regarding the use of at least one medication was 83%. Medications for the cardiovascular system were the most prevalent, followed by the dietary tract, and metabolism and nervous system. The large amount of drugs used for Chronic Non-Communicable Diseases stands out, thus, the importance of comprehensive health care for the elderly is highlighted.